PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MAHASISWA PGSD FIP UNIMED - Simanjuntak, Sorta; Tamba, Robenhart (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
This research aims to: develop a problem-based learning model to improve students' creative thinking. The subjects of this study were fifth semester PGSD students in 2021/2022 with a quasi-experimental design. The research method uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The data collection tools are questionnaires, observation sheets and tests. The data were analyzed by descriptive percentage and continued with the inferential statistical test through the t test. The results of the descriptive analysis stated that: (1) the feasibility of the model based on the average value of the design test and material test was 91% in the very feasible category; (2) practicality gets a percentage of 91% in the very practical category without any revisions; and (3) the effectiveness of the module through: a) the RPCPM control class gets a percentage score of 77% in the pretty good category and the experimental class gets a percentage score of 85% in the very good category; b) PKBK control class 70% quite complete category while the experimental class 90% with very complete category. That is, the average CPM value of the experimental class: 93 and the control class: 88.70 is significantly different.